Distal arch replacement for aortic aneurysm associated with pseudocoarctation through the L-incision approach. (13th April 2022) - Goto, Takuya; Koizumi, Junichi; Saiki, Hirofumi; Kin, Hajime
Abstract: We report the case of a 16-year-old boy in whom we successfully repaired a distal aortic arch aneurysm associated with pseudocoarctation using double aortic cannulation and antegrade selective cerebral perfusion through the L-incision approach. This approach provided excellent exposure from the ascending aorta to the descending aorta, which enabled total body perfusion. We avoided cardiac arrest and hypothermic circulatory arrest during the surgery. The L-incision approach could be a better alternative for aortic arch surgery in adolescents. Abstract : Pseudocoarctation of the aorta is a rare congenital anomaly characterized by kinking and buckling of the aorta without stenosis.